Predictors of Condom Use in a Multi-Site Study of High-Risk Youth Living with HIV - Outlaw, Angulique (2010)
Risky sexual behavior among youth living with HIV (YLH) must be addressed to prevent the spread of the disease. The purpose of the current study was to investigate factors associated with condom use in a multi-site sample of YLH (ages 16-24). Baseline assessments were conducted with 186 YLH using a computer assisted personal interviewing (CAPI) method. Path analysis suggested that condom use was directly predicted by motivational readiness and self-efficacy for safer sex. Interventions that promote self-efficacy and motivational readiness through a variety of mechanisms may be useful in understanding and conceptualizing sexual risk behavior in YLH. However, further predictors must be studied to account for more variance.